Systematic bias and the phylogeny of Coleoptera—A response to Cai et al. (2022) following the responses to Cai et al. (2020). (27th October 2022) - Boudinot, Brendon E.; Fikáček, Martin; Lieberman, Ziv E.; Kusy, Dominik; Bocak, Ladislav; Mckenna, Duane D.; Beutel, Rolf Georg
Abstract: Systematic bias is one of the major phylogenetic issues arising over the last two decades. Using methods designed to reduce compositional and rate heterogeneity, hence systematic bias, Cai and co‐workers (2022) (= CEA22) reanalyzed the DNA sequence dataset for Coleoptera of Zhang et al. (2018) (= ZEA). CEA22 suggest that their phylogenetic results and major evolutionary hypotheses about the Coleoptera should be favoured over other recently published studies. Here, we discuss the methodology of CEA22 with particular attention to how their perfunctory reanalysis of ZEA obfuscates rather than illuminates beetle phylogeny. Similar to published rebuttals of an earlier study of theirs, we specifically find that many of their claims are misleading, unsupported, or false. Critically, CEA22 fail to establish the stated premise for their reanalysis. They fail to demonstrate how composition or rate heterogeneity supposedly impacted the phylogeny estimate of ZEA, let alone the results of other recent studies. Moreover, despite their claim of comprehensive sampling of Coleoptera, their dataset is neither the most diverse with respect to species and higher taxa included, nor anywhere near the largest in terms of sequence data and sampled loci. Although CEA22 does contribute additional fossils for calibration, those seeking the best available estimate for Coleoptera phylogeny and evolution based on molecular data are advised to look elsewhere. Abstract : Major claims of Cai et al. (2022) et al. on beetle evolution are not justified A placement of Adephaga as sister of the other suborders is unsupported An aquatic origin of Coleoptera does not appear likely